Foreign Workers in Korea: Issues and Discussions - Seol, Dong-Hoon (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 1 (2000): Economies in Flux, 2009)
The Korean economic miracle of the 1980s drastically altered the regional labor landscape. Once a major labor exporter, Korea has become a prime destination for migrant workers from developing countries due to a severe shortage of unskilled production workers in small- and medium-size industries. Also, Korean workers had developed the so-called "3-D syndrome," an aversion to difficult, dangerous and dirty jobs in factories and sought relatively higher-paying employment in the construction sector. Of the three types of migrant workers ñ the legal employee, the industrial and technical trainee and the undocumented migrant worker, the latter two, in general, are made to endure long working hours, low wages and poor working conditions. In some cases, the trainees receive the least in terms of wages, even less than the undocumented worker because of the Industrial and Technical Training Program for Foreigners (ITTP). The ITTP prevents them from acquiring proper working status and benefits. However, undocumented workers have the least protection from abuse since employers routinely threaten them with deportation. Protests in the mid-1990s forced the implementation of a measure ordering employers to pay at least the minimum wage directly to the workers, reducing the chances of exploitation by agencies handling remittances. In 1998, the Working After Training Program for Foreigners (WATP), which allowed trainees who pass certain skills tests after a two-year period to enjoy workers' rights under the Standard Labor Act and the Minimum Wages Act, was introduced amid protest that it was as flawed as the ITTP. Government likewise announced its intention to strengthen the monitoring of undocumented migrant workers and freeze the total quota of trainees. Pro-migrant workers activists are seeking the implementation of the Employment of Foreign Workers Act as an alternative scheme to maximize the economic benefits from the inflow of unskilled migrant workers without discriminating against them economically and socially. But the future of this proposed legislation is uncertain.